Sprouty 4 expression in human oral squamous cell carcinogenesis - Pei-Hsien Liao; Fu-Hsiung Chuang; Yen-Yun Wang; Wen-Chen Wang; Chiang-Wei Su; Ching-Wei Hsu; Shyng-Shiou Yuan; Yuk-Kwan Chen (Journal of Dental Sciences, 2023)
Background/purpose: Reviewing literature, sprouty 4 (SPRY4) has not been studied in human oral squamous cell carcinomas (OSCCs). The study aimed to examine SPRY4 expression in human oral squamous cell carcinogenesis. Materials and methods: A total of 95 OSCCs, 10 OPMDs with malignant transformation (MT), 17 OPMDs without MT, and six normal oral mucosa (NOM) samples were recruited for immunohistochemical staining; three OSCC tissues with normal tissue counterpart NOM were employed for Western blotting. Three human oral cancer cell lines (OCCLs), an oral precancer cell line (dysplastic oral keratinocyte, DOK), and a primary culture of normal oral keratinocytes (HOK) were used for Western blotting; OCCLs and HOK were employed for real-time quantitative reverse transcription-polymerase chain reaction. OCCLs were evaluated in terms of proliferation, migration, and invasion assays. Results: SPRY4 protein expression was significantly increased in OSCCs compared with NOM. Protein and mRNA SPRY4 expression in OCCLs were significantly elevated compared with HOK. Significant increases in the degrees of proliferation, migration, and invasion were noted in OCCLs with SPRY4 siRNA transfection compared with those without transfection. SPRY4 protein level was increased in OPMD with MT compared to OPMD without MT. SPRY4 protein was significant increase in DOK in comparison with HOK. SPRY4 protein expression was significantly increased from NOM and OPMD without MT to OSCC. SPRY4 protein expression in OCCLs was significantly enhanced compared with DOK and HOK respectively. Conclusion: Our results indicate that SPRY4 expression is possibly involved in human oral squamous cell carcinogenesis.